On Prophets, Warriors, and Kings - Brooke, George J.,Feldman, Ariel (De Gruyter, 2016)
In response to the growing interest in the history of biblical interpretation, this volume brings together a variety of studies exploring ways in which ancient and modern readers, Jewish and Christian, understood the Prophetic Books. With a particular emphasis on significant figures in the Former Prophets, these essays engage their interpretation in such literary corpora as the Hebrew Bible, the Dead Sea Scrolls, and the New Testament.
9783110392913
Keywords: Rezeption; Frühjudentum; Frühchristentum; Literatur